Islamic Banking Innovation and Customer Satisfaction: A Case Study of Indonesia and Nigeria - Yarmanti A., Violla; Wissalam Bustami, Alek; Muhammad Ardo, Adam (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose - The study examines the impact of digital accessibility, transparency, security, and product innovation on consumer trust and engagement. Method - This study utilizes a qualitative research methodology, incorporating in-depth interviews and thematic analysis to extract insights from Islamic banking clients and industry specialists. The data gathering emphasizes consumer experiences, opinions of service quality, and expectations for digital financial services Findings - The results demonstrate that users of Islamic banking prioritize service quality, security protocols, and digital accessibility. Customers demonstrate a pronounced inclination towards mobile banking services that incorporate sophisticated yet intuitive features, as well as more transparency in financial transactions and investment methodologies. Moreover, proficient risk management and the use of fintech technologies enhance client trust and happiness Practical Implication - enhance consumer behavior theories in Islamic banking, highlighting the relationship between technology adoption, institutional trust, and Sharia compliance. An immediate necessity for Islamic banks to invest in digital security, improve financial transparency, and create innovative Sharia-compliant financial products Originality/value - an innovative comprehensive analysis of the convergence of Islamic banking services, technology progress, and consumer expectations by incorporating numerous variables, including security, transparency, and innovation, into a coherent framework